Design and Comprehensive Multiphysics Analysis of Permanent Magnet Synchronous Motor for Podded Propulsion in Marine Applications - Jang-Hyun Park; Yeon-Ho Jeong; Do-Kwan Hong (IEEE Open Journal of the Industrial Electronics Society)
This article presents the design and comprehensive multiphysics analysis of a permanent magnet synchronous motor (PMSM) intended for small electric podded propulsion systems in marine applications. Minimizing vibration related to underwater radiated noise (URN) and ensuring thermal stability to allow prolonged continuous operation are crucial aspects of propulsion motor design. To reduce URN, particular attention is given to the stator vibration mode order, determined by the slot/pole combination (SPC) of the PMSM. Structure-borne noise analysis is used to evaluate the equivalent radiated power level of three designed PMSMs with different stator vibration mode orders. One-way multiphysics analysis using finite element analysis (FEA) is performed in a water environment for the finally-selected PMSM with pod housing structure. URN generated from the electromagnetic force is predicted by structural-acoustics analysis. Through lumped-parameter thermal network (LPTN) and computational fluid dynamics (CFD) analyses, it is proposed that, based on the cylindrical housing shape, the thermal stability of the podded propulsor can be evaluated using LPTN analysis instead of CFD analysis. A prototype motor is fabricated to validate the results obtained using FEA.